Marketing process of sewing thread supplying industry of Bangladesh: a study on Coats Bangladesh Ltd. - Islam, Md.Shariful (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2014.